Phương pháp thiết kế giá kì vọng cho hệ thống với thông số bất định - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper presents a method of designing a quadratic optimal output feedback control system with generalized parameter uncertainly. For the case of discrete probability distribution of system parameters in uncertainty domain an algorithm is given.